2021
DOI: 10.1177/1932202x211018644
|View full text |Cite
|
Sign up to set email alerts
|

Engagement in Learning Physics Through Project-Based Learning: A Case Study of Gifted Finnish Upper-Secondary-Level Students

Abstract: Research on the advantages and disadvantages of project-based learning (PBL) among gifted pupils studying physics is scarce. This mixed-methods study investigates engagement, experiences, and learning outcomes among gifted Finnish upper-secondary-level students learning physics through PBL. A six-lesson PBL module on basic Newtonian mechanics was designed and implemented for a group of gifted students ( N = 38), whereas a traditional teacher-driven approach was used among a control group ( N = 38) of gifted st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
0
8
0
1
Order By: Relevance
“…The findings of French et al (2011) revealed that while gifted students demonstrate a preference for studying alone, they are more willing to collaborate with others if they believe their work is appreciated by their peers. In the study by Makkonen et al (2021), more than 80% of the gifted students found that collaboration with like-ability peers was beneficial when utilizing project-based learning in physics. Teamwork, however, can sometimes present challenges: the findings of Kuusisto and Tirri (2015) revealed that disagreements between gifted science students can escalate into non-constructive conflicts.…”
Section: Talent Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of French et al (2011) revealed that while gifted students demonstrate a preference for studying alone, they are more willing to collaborate with others if they believe their work is appreciated by their peers. In the study by Makkonen et al (2021), more than 80% of the gifted students found that collaboration with like-ability peers was beneficial when utilizing project-based learning in physics. Teamwork, however, can sometimes present challenges: the findings of Kuusisto and Tirri (2015) revealed that disagreements between gifted science students can escalate into non-constructive conflicts.…”
Section: Talent Developmentmentioning
confidence: 99%
“…Potentially engaging pedagogical approaches for teaching physics to gifted students have also been developed. More specifically, inquiry-based learning approaches, such as project-based learning, have proven useful in developing talent in physics among gifted lower and upper secondary students (Langbeheim, 2015;Makkonen et al, 2021). Likewise, problem-based learning has been shown to improve gifted elementary students' achievements in science units that include physics content (Robinson et al, 2014).…”
Section: Talent Developmentmentioning
confidence: 99%
“…Many schools and universities are now utilizing digital technology and multimedia to aid in visualizing difficul and abstract physics concepts (Rahim et al, 2022;Sunaryo et al, 2022). Furthermore, many physics teachers are adopting project-based approaches (Yanti et al, 2019;Widyaningsih & Yusuf, 2019;Santyasa et al, 2020;Makkonen et al, 2021) and problem-based approaches (Fauzana, et al, 2019;Pane et al, 2021;Kanyesigye et al, 2022a;Kanyesigye, et al, 2022b;Fonseca et al, 2022) to motivate students and help them better understand physics concepts.…”
Section: Introductionmentioning
confidence: 99%
“…By involving students in collaborative investigations of real-world problems, PjBL facilitates active and profound learning (Belwal et al, 2020;Gendjova & Yordanova, 2009;Hong Sharon Yam et al, 2010;Papanikolaou & Boubouka, 2010). The performance and engagement of students in physics studies experience a substantial impact through the adoption of PjBL (Araujo et al, 2021;Bobroff & Bouquet, 2016;Makkonen et al, 2021) In light of this, the evolution of the Internet and mobile platforms has created opportunities for hybrid learning, which combines both online and in-person interactions between educators and students. The COVID-19 pandemic has accelerated the integration of technology into physics education, underscoring the need for adaptive and flexible teaching strategies.…”
Section: Introductionmentioning
confidence: 99%